Pathoetiology of multiple sclerosis: are we barking up the wrong tree? - Stys, Peter K. (Faculty of 1000 Ltd, 2013)
Despite a century of intensive investigation, the underlying cause of multiple sclerosis has eluded us. It is clear that there exists a prominent progressive degenerative phenotype together with an important autoimmune inflammatory component, and careful histopathological examination always shows, to a greater or lesser degree, concomitant degeneration/demyelination and adaptive T cell-dependent immune responses. Given this picture, it is difficult, if not impossible, to definitively say whether degeneration or autoimmunity is the initiator of the disease. In this review, I put forward the evidence for and against both models and speculate that, in contrast to the accepted view, it is equally likely that multiple sclerosis may be a degenerative disease that secondarily elicits an autoimmune response, and suggest how this might influence therapeutic approaches.